Peran Organisasi IPM dalam Menumbuhkan Karakter Muhammadiyah di Pondok Pesantren - Hayyun Nur Diniah; Fitri Nur Mahmudah (Jurnal Syntax Admiration, 2023)
Facing this era of disruption, schools are obliged to involve the whole community in schools, such as organizations, administrators, educators, students, and school principals, and for Islamic boarding schools there is a need for involvement by the kyai and existing dormitory administrators. The role of IPM (Muhammadiyah Student Association) in shaping the character of Muhammadiyah in Islamic Boarding Schools through the many contributions and activities that are in it, apart from the aspect of worship or in terms of independence, there is also in terms of its organization and from its own basis This research uses a descriptive qualitative approach which is a research strategy in which researchers investigate events, phenomena in the lives of individuals and ask a person or group of individuals to tell their lives. This information is then retold by the researcher in a descriptive chronology. The results of this research include: the role of the Muhammadiyah Student Association, IPM performances, IPM Implementation, IPM Urgency, IPM Ideals, IPM Positive Impacts, and IPM Provisions in the future. All of the results of this research are aimed at cultivating Muhammadiyah character in SMA Muhammadiyah 2 Al-Mujahidin with the nuances of Islamic boarding schools.